2022
DOI: 10.3389/fcimb.2022.884298
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition of Anti-Cytomegalovirus Immunoglobulin G Levels and the Risk of 9 Cardiovascular Diseases

Abstract: BackgroundAccumulating evidence has indicated that persistent human cytomegalovirus (HCMV) infection is associated with several cardiovascular diseases including atherosclerosis and coronary artery disease. However, whether there is a causal association between the level of anti-HCMV immune response and the risk of cardiovascular diseases remains unknown.MethodsSingle-nucleotide polymorphisms associated with anti-cytomegalovirus immunoglobulin (Ig) G levels were used as instrumental variables to estimate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…At last, some studies suggest that race and ethnicity play a role in the risk of VTE. 48 49 50 It is reported that the mutations in the genes encoding anticoagulants are the main genetic cause of PE in Asia. 49 However, these mutations can only account for 12.04% of VTE patients.…”
Section: Discussionmentioning
confidence: 99%
“…At last, some studies suggest that race and ethnicity play a role in the risk of VTE. 48 49 50 It is reported that the mutations in the genes encoding anticoagulants are the main genetic cause of PE in Asia. 49 However, these mutations can only account for 12.04% of VTE patients.…”
Section: Discussionmentioning
confidence: 99%
“…The primary analysis was inverse variance weighted (IVW) MR under a random-effect model, which assumed all genetic variants as valid instruments. Weighted median and MR-Egger methods were also performed [ 14 , 15 ]. The weighted median method can reveal consistent estimates even if up to 50% of the weight in the MR analysis comes from invalid genetic variants [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…All of our data were obtained from published studies, which were supported by the institutional review committee, and informed consent was obtained from the participants in their original research [ 27 , 28 ]. Thus, further sanctions were not needed.…”
Section: Data Availability and Ethical Approvalmentioning
confidence: 99%